DAMPAK KEIKUTSERTAAN INDONESIA DALAM KEANGGOTAAN G20 TERHADAP HUBUNGAN INDONESIA-ARAB SAUDI TAHUN 2007-2011 - Oscar Angga Pradhipta; Syafri Harto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research discusses about the impact of Indonesia's participation in the G-20 membership of the relationship between Indonesia and Saudi Arabia 2007-2011. G-20 is a group of economic cooperation between developed countries and developing countries. As an economic forum, the G-20 more into the arena of consultation and cooperation matters related to the international monetary system. Impact of Indonesia's participation in the G-20 membership put to good use as a platform to promote the country to improve the economy and the welfare state and place for diplomacy, increase foreign confidence in the ability of Indonesia in terms of exports and imports. So that makes Saudi Arabia increase its cooperative relations with Indonesia.The author analyzes this case by finding data and facts gathered through some literature from books, journals, and websites. Concepts used in analyzing the impact of Indonesia's participation in the G-20 membership of the relationship between Indonesia and Saudi Arabia 2007-2011 is the concept of the national interest and the concept of international cooperation.This research shows that the impact of Indonesia's participation in the G-20 membership of the relationship between Indonesia and Saudi Arabia in 2007-2011 was Indonesia can exploit this situation to improve economic relations with Saudi Arabia were also fellow members of the G-20, especially in terms of oil imports.Keywords: Impact, G-20, International Cooperation, Saudi Arabia, Imports, Oil.